The teachers’ perceptions on the implementation of inclusive policy of special needs learners in Gweru District Primary Schools. - Mawocha, Nency (Midlands State University, 2017)
A variety of researches have been carried out on education of the special needs children, and little have been done to find out the perceptions of teachers towards the implementation of the Inclusive policy of special needs learners ever since the introduction of the inclusive education. This research specifically focused much on the teachers’ perceptions on the implementation of the inclusive policy of special needs learners in Gweru District primary schools. The research methodology was underpinned by descriptive survey. Questionnaires were administered to primary teachers while schools heads responded to face-to-face interviews. Data collected was represented thematically in tables and verbatim. The research revealed some adequacies on the effective inclusion. Children with special needs are still experiencing inequality in terms of lack of resources. There is need for teachers to be fully trained in special needs both theoretically and practically. The researcher concluded that there is inadequate stakeholder participation to ensure availability of equipment and materials to ensure effective learning of special needs learners. The study recommended that teachers training as well as in-service training take a bias towards inclusive education. It was also recommended that various stakeholders be given opportunity to participate in the implementation of inclusive education.